Learning of Teaching in the Professional Socialization in Physical Education - Souza Neto, Samuel De; Iza, Dijnane Fernanda Vedovatto; Silva, Mellissa Fernanda Gomes Da (Universidade Estadual Paulista, 2017)
AbstractAIMS to investigate how the professional socialization happens through teacher education.METHODS a qualitative research, descriptive, was developed using exploratory interview and narrative interview to clarify and deepen the collected information. Two Physical Education teachers with different stories of personal and professional development participated in this study. Through content analysis the data was organized in themes: the cultural capital and the learning of teaching, as a social, spatial and temporal process; a cognitive, plural and heterogenic process and a human, moral and relational process.RESULTS life settings can be viewed as the building scaffoldings of a professional socialization with the aim of understanding teachers and their practices in the knowledge of their lives, as influenced by social interactions. In this process of successive socializations, teachers build their professional identity, valuing social interactions in the environments they inhabit. In this study, practice was viewed as a site for training, the production of knowledge, and professional socialization in the acquisition of cultural capital. The knowledge of teachers was conceived as having a social nature, bringing underlying sources of acquisition associated with the family, school, and university because they decisively contribute to the structure of the educational practice.CONCLUSION the professional socialization is a dynamic process which involves not only the learning, but the acquisition of a professional ethos and, mainly, a teacher's identity and a base of knowledge that support the social interaction and the teaching culture in the activities and individual socialization in the habitus perspective.
Keywords: teaching; professional learning; professional development; professional identity